WAYANG WONG LANGEN LESTARI BUDOYO DONOMULYO SEBUAH KAJIAN GAYA WAYANG WONG PEDESAAN - Mr. Surojo (Joged, 2012)
Wayang wong Lestari Budaya Donomulyo who was born and developed in rural communities Donomulyo an individual and collective expression of the rural art style. This Wayang wong was founded in1932 by R. Sanghadi as a palace of Yogyakarta Sultanate courtiers.This transformation and culture ofpalace formality was a cultural diffusion of the cultural center of the (palace) to a small cultural center(rural), thus giving birth to an art style that is different from the original. This diffusion certainly related tothe role Kridha Beksa Wirama in 1918 as an arts institution devoted to the general public, including peoplefrom the countryside The rural of wayang wong is a rustic contemporary art form of the distribution and development of theforegoing, where the elements that influence complex either in a linear kesejarahannya of Kridha BeksaWirama and social culture. That is, in the process of formation of wayang wong arable quality, especiallychoreography has a unique claim as the expression of which is produced by the artist that is a blend of rusticpalace of art with the art of rural tradition "ndeso". This traditional art is an art form that originates andstems as well have been perceived as belonging to the arts community. Hasil accepted as tradition, theinheritance devolved from the older to the younger generation. Keyword : wayang wong, traditional, rural style, the diffusion